Thugs rje chen poʼi rnam thar Phan you gsal byed sgron ma : a presentation of the practice focussing upon Avalokiteśvara Mahākāruṇika - Ke-tu-seṅ-ha (Jamyang Samten and Trayang, 1974)
Background text for understanding the Lamaist contemplative practice focussing upon Avalokiteśvara in the form Mahākāruṇika as tutelary deity.